Why Did the Canary Die? (Sergei Yesenin about Nikolai Klyuev) - I. V. Kudryashov; S. N. Pyatkin (Научный диалог)
The article is devoted to the problem of interpretation of the well-known Yesenin lines about N. A. Klyuev in the poem “In the Caucasus”. In literary criticism, the point of view has been established, according to which the eleventh verse of the poem by S. A. Yesenin contains a well-known “epigrammatic definition” expressing the extremely sharp “negative attitude” of the poet towards his former mentor. The systemic analysis of Yesenin’s poetic definitions of Klyuev, “gentle apostle” (“O muse, my flexible friend...”, 1917) and “Ladoga deacon” (“In the Caucasus”, 1924) in the historical and literary context, made it possible to find their close semantic correlation and identify the lines about Klyuev in the poem “In the Caucasus” as the author’s self-irony, expressed in the form of a comic demotion of his former teacher. It is proved that in the poem “In the Caucasus”, ironically putting himself in the place of a “dead canary”, a poet who categorically does not accept imitation in poetry, not only declares that singing “from the voice of someone else” is destructive for any talent, but also clearly makes it known that he is “not a canary,” imitating Klyuev, that their paths diverged long ago, that the canary in him “died” in his youth; and the self-ironic, harmless lines about his mentor in the poem “In the Caucasus” testify to Yesenin’s creative maturity as a great national poet who has comprehended his significance and place in Russian Parnassus.